Irradiation crosslinking collagenous fiber material and preparation method and application thereof
By introducing organic solvents and dispersants into collagen fibers, controlling the irradiation conditions, achieving uniform cross-linking of collagen, solving the problem of insufficient enzymatic resistant ability of collagen materials, and obtaining collagen fiber materials with high mechanical strength and enzymatic resistant properties, which are suitable for biomedical applications.
Patent Information
- Application Number
- CN202510139530.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-08
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2045-02-08
AI Technical Summary
The existing collagen materials have insufficient ability to resist enzymatic decomposition in biomedical applications, and physical crosslinking methods have problems such as limited crosslinking strength, unevenness and structural damage.
By introducing organic solvents and dispersants into collagen fibers, irradiation conditions (such as irradiation dose, temperature and solvent system) are controlled, uniform cross-linking of collagen is achieved, and collagen fiber materials with high mechanical strength and enzymatic resistance are formed.
The obtained irradiated crosslinked collagen fiber material has good mechanical properties, enzymatic resistance and biocompatibility. It is suitable for tissue engineering scaffolds and medical injection fillers, and has no chemical crosslinking agent residue and is highly safe.
Smart Images

Figure CN119613775A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of organic polymer compound processing and also to the field of medical material technology, in particular to a radiation cross-linked collagen fiber material and a preparation method and application thereof. Background Art
[0002] Collagen is a natural biopolymer material with excellent biocompatibility and biodegradability, and is widely used in the biomedical field. Its unique molecular structure and biological properties enable it to show good cell affinity in terms of cell adhesion, proliferation and differentiation, which helps promote tissue regeneration and repair. Due to these characteristics, collagen materials are particularly suitable as the basic material of tissue engineering scaffolds, providing cells with an ideal growth microenvironment, thus showing important application potential in the repair and regeneration of tissues such as cartilage, skin, and bone.
[0003] However, due to the presence of specific enzymes targeting collagen in the human body, pure collagen materials have poor resistance to enzymolysis, which limits their long-term stability in biomedical applications. In order to improve the mechanical properties and resistance to enzymolysis of collagen, it is usually modified by cross-linking. However, commonly used chemical cross-linking agents often bring about residue problems and pose potential safety risks. Therefore, physical cross-linking methods are widely used as an alternative, but there are still some shortcomings. Conventional material cross-linking methods, such as ultraviolet irradiation, high temperature, freeze-drying and other methods, have problems such as limited cross-linking strength, uneven cross-linking, and destruction of collagen structure.
[0004] During the irradiation process, high-energy rays (such as gamma rays or electron beams) react with water molecules to produce a large number of free radicals (such as hydroxyl radicals and hydrogen radicals). These free radicals can attack the amino acid residues in the collagen molecules, especially the charged groups such as lysine, arginine, and glutamic acid. These reactions can trigger the chemical bond reorganization of collagen and promote covalent cross-linking between proteins. Under the catalytic action of free radicals, the collagen molecules form cross-links between molecular chains through covalent bonds to generate a larger protein network structure. This cross-linking will significantly increase the strength and elasticity of collagen, and is particularly suitable for biomaterials that need to maintain structure for a long time, such as tissue engineering scaffolds.
[0005] At present, irradiation is mainly used for protein sterilization. Under conventional irradiation, the electron beam excites the formation of free radicals too quickly, causing local rapid cross-linking of collagen, resulting in uneven cross-linking of materials, hardening and brittle materials, protein denaturation and other problems, making it impossible to use them normally. Summary of the invention
[0006] The object of the present invention is to provide a method for preparing a collagen fiber material without introducing exogenous substances for irradiation and effectively preventing local rapid cross-linking of collagen caused by irradiation; another object of the present invention is to provide a collagen fiber material prepared based on the aforementioned method and having good uniformity within a specific cross-linking degree range; another object of the present invention is to provide the use of the aforementioned collagen fiber material in the preparation of medical injectable filling materials and / or tissue engineering scaffolds.
[0007] In a first aspect, the present application provides a method for preparing a radiation cross-linked collagen fiber material: A method for preparing a radiation cross-linked collagen fiber material comprises the following steps: (1) Preparation of collagen fiber intermediates: Dispersing concentrated collagen fibers in an irradiated solvent system, and obtaining collagen fiber intermediates with a concentration of 35-45 mg / ml after centrifugation; the irradiated solvent system comprises physiological saline and an organic solvent in a volume ratio of 1:(1-2.4), and a dispersant with a total amount of 0.1-2 w / v% of the physiological saline and the organic solvent; (2) irradiation cross-linking: irradiating and cross-linking the collagen fiber intermediate at a temperature of 20-30° C. and an irradiation dose of 10-20 kGy to obtain cross-linked collagen fibers; (3) removing the dispersant from the cross-linked collagen fibers and sterilizing them by low-temperature irradiation to obtain a finished collagen fiber material.
[0008] Furthermore, in the preparation of the collagen fiber intermediate, the liquid ratio of the concentrated collagen fiber to the irradiated solvent system is 1:20-1:50.
[0009] The irradiation solvent system contains a relatively high proportion of organic solvents, which can effectively disperse collagen fibers and reduce the concentration of water molecules in the material, thereby reducing the rate of free radical excitation during irradiation, thereby slowing down the cross-linking of collagen fibers by irradiation. The addition of a dispersant can prevent excessive cross-linking between monomers during subsequent irradiation cross-linking, thereby preventing the formation of a high-strength scaffold structure in the shape of a body, thereby facilitating subsequent homogeneous dispersion. The collagen concentration is controlled between 35-45 mg / ml. Too low a concentration will result in insufficient cross-linking of the irradiated material, while too high a concentration will result in excessive cross-linking.
[0010] Irradiation at room temperature of 20-30 ℃ can achieve local cross-linking between collagen fibers in a short range when the collagen fibers are in a slightly fluid state, thereby improving the mechanical properties and resistance to enzymatic hydrolysis of the collagen fibers. Irradiation doses of 10 / 15 / 20 kGy can achieve in vivo degradation times of 6 months / 9 months / 15 months respectively. If the temperature is too low during irradiation cross-linking, the degree of cross-linking may be insufficient and the resistance to enzymatic hydrolysis may decrease; if the irradiation intensity is too high, it may cause excessive cross-linking.
[0011] The free radicals generated during the radiation cross-linking process covalently cross-link the amino acids of the collagen side chains to improve the fiber performance. The prepared radiation cross-linked collagen fiber material does not contain any cross-linking agent and is a pure collagen material. The homogenization process after irradiation uniformly plasmidizes the collagen fibers, which have high mechanical strength, greatly increased physical and chemical properties and resistance to enzymolysis, and are suitable for application in tissue engineering scaffold materials. The material is injectable and can still be evenly and smoothly injected with a 27G syringe needle after cross-linking, and the in vivo degradation cycle is controllable. The radiation cross-linked collagen fiber material prepared by the present invention can also be freeze-dried. The freeze-dried radiation cross-linked collagen fiber material has excellent hemostatic properties and the effect of inducing cell proliferation, and is suitable for use in the field of tissue regeneration and repair.
[0012] The concentrated collagen fibers include any one or more combinations of type I collagen fibers, type II collagen fibers, and type III collagen fibers.
[0013] Furthermore, concentrated collagen fibers can be obtained from the collagen self-assembly precipitation process; The specific operation of the collagen self-assembly precipitation process is to regulate the collagen solution to the in vitro physiological state for self-assembly, pH 6.4-7.8, temperature 35-38 ° C, sodium chloride concentration 0.1-0.2 M, standing time 2-3 h, to achieve the precipitation of collagen fibers; then the precipitated collagen fibers are homogenized and dispersed, and then obtained by centrifugation.
[0014] Furthermore, the radiation crosslinking is electron beam irradiation or gamma ray irradiation.
[0015] Furthermore, electron beam irradiation is used, and the thickness of the collagen fiber intermediate does not exceed 10 mm during irradiation.
[0016] Further, the organic solvent includes but is not limited to any one or more combinations of dimethyl sulfoxide, isopropanol, acetone, ethyl acetate, and methyl tert-butyl ether. As a preferred embodiment of the present invention, the organic solvent includes dimethyl sulfoxide.
[0017] Dimethyl sulfoxide is a commonly used organic solvent that can be miscible with physiological saline and the added dispersant in any proportion. Collagen fibers can exist stably in the configured organic solvent system without destroying the triple helix structure of the collagen molecule.
[0018] Furthermore, the dispersant includes any one or more combinations of Triton X-100, Triton X-114, Triton X-405, and TritonGR-7M.
[0019] As a nonionic surfactant, Triton X-100 can effectively improve the dispersion of collagen fibers in the solution system and avoid excessive cross-linking of collagen fibers during irradiation.
[0020] Furthermore, the method for removing the dispersant in step (3) includes: re-dissolution, homogenization and / or ultrasonic treatment, and centrifugation.
[0021] Specifically, the method for removing the dispersant in step (3) comprises: adding physiological saline to the cross-linked collagen fibers, with the liquid ratio controlled at 1:20-1:50, homogenizing and dispersing for 30 minutes, ultrasonically extracting for 30-60 minutes, and centrifuging; and repeating the operation multiple times.
[0022] Furthermore, the cross-linked collagen fibers are first subjected to ultra-low temperature quick freezing treatment, and then subjected to low-temperature irradiation sterilization treatment at a temperature range of -40--80°C; the irradiation dose of the low-temperature irradiation sterilization treatment is 25-30 kGy.
[0023] In low-temperature irradiation sterilization, the irradiation process keeps the material in a low-temperature frozen state, preventing further cross-linking between collagen fibers during subsequent irradiation and causing changes in fiber particle size. At the same time, the irradiation dose can achieve sterilization of the material without changing its physical and chemical properties.
[0024] Furthermore, in the preparation of the cross-linked collagen fibers, the thickness of the collagen fiber intermediate is 5-8 mm; in the low-temperature irradiation sterilization, the thickness of the cross-linked collagen fibers is 5-8 mm.
[0025] As an optional implementation, the collagen fiber intermediates are packaged in aluminum foil bags with a thickness of 5-8 mm and irradiated, so that the radiation dose received by the collagen is uniform and the cross-linking degree of the collagen fibers on the upper and lower surfaces of the aluminum foil bag is consistent.
[0026] Furthermore, in the ultra-low temperature quick freezing, the ultra-low temperature is -80°C.
[0027] Furthermore, in the preparation of the irradiated cross-linked collagen fiber material, the thawing process is as follows: First place it in a 25 ℃ constant temperature box and let it stand for 20 min, then shake it for 1 min, then place it in a 25 ℃ constant temperature box and let it stand for 20 min, repeat at least 2 times until it is completely thawed.
[0028] Direct thawing will cause the saline in the material to precipitate first. The increase in local collagen fiber concentration will cause the particle size of the material to change. Repeated shaking during the thawing process will allow the thawed saline to quickly return to the system, making the material thawed more evenly.
[0029] The present application provides a radiation cross-linked collagen fiber material and a preparation method thereof. To address the problem of excessively rapid cross-linking of proteins caused by the radiation process, the solvent system of the collagen fibers is changed, some organic solvents are introduced, and the moisture content is reduced to control the excitation rate of the electron beam on water molecule free radicals, thereby controlling the degree of cross-linking of the collagen material by radiation; further, uniform cross-linking of the collagen fibers is achieved by introducing a dispersant and controlling processes such as the radiation dose, radiation temperature, and material thickness.
[0030] In a second aspect, the present application provides a collagen fiber material: A collagen fiber material, the collagen fiber material prepared by the above method, has the following characteristics: The average particle size of the collagen fibers is in the range of 100-150 μm.
[0031] The material was filled into a 27 G syringe, and the maximum pushing force was between 11.5 N and 25 N at a pushing speed of 30 mm / min.
[0032] The collagen fiber material prepared in the present application has good mechanical properties and resistance to enzymatic degradation. The complete degradation period in vivo can be adjusted by the irradiation dose, and the complete degradation time in vivo can be controlled between 6-15 months. Furthermore, the collagen fibers are not cross-linked using any chemical cross-linking agent, and the prepared material is pure collagen fibers and physiological saline without any other substances, and has high biological safety.
[0033] In a third aspect, the present application provides an application of a collagen fiber material: The collagen fibers obtained by the present invention can be directly thawed and used as gel injection filling. The excellent biocompatibility and resistance to enzymolysis can be used in the fields of skin tissue filling, soft tissue repair, joint injection, drug carrier, etc.
[0034] The collagen fibers obtained by the present invention can be used as tissue engineering scaffolds after freeze-drying, and can be used in the fields of burn dressings, tissue hemostasis, soft tissue reconstruction, etc.
[0035] Beneficial effects: 1. The present invention adopts a special irradiation solvent, and the organic solvent and dispersant in the special irradiation solvent can effectively disperse the collagen fibers, and at the same time reduce the concentration of water molecules in the material, so that the excitation rate of free radicals during the irradiation process is reduced, thereby slowing down the cross-linking of the collagen fibers by irradiation, and thus obtaining more uniform cross-linked collagen fibers; further control the material concentration before irradiation to 35-45 mg / ml, and irradiate at room temperature (20-30 ℃) and under the conditions of the preferred irradiation dose, so as to achieve uniform cross-linking of the collagen fibers, so that the collagen material has a slight fluidity state for cross-linking, and realizes short-range and relatively uniform local cross-linking between the collagen fibers, so that the obtained irradiated cross-linked collagen fiber material has a high degree of cross-linking, enzymolysis resistance and uniform and smooth injection performance of 27G syringe needle.
[0036] 2. The present application adopts low-temperature irradiation sterilization treatment at -40-80°C to achieve thorough sterilization of cross-linked collagen fibers. At the same time, deep low temperature can prevent further cross-linking of collagen fibers and affect their physical and chemical properties.
[0037] 3. The collagen fibers obtained by the present invention can be directly thawed and used as gel injection filling. Due to its excellent biocompatibility and resistance to enzymolysis, it can be used in the fields of skin tissue filling, soft tissue repair, joint injection, drug carrier, etc.; the collagen fibers obtained by the present invention can be used as tissue engineering scaffolds after freeze-drying, and can be used in the fields of burn dressings, tissue hemostasis, soft tissue reconstruction, etc. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] Figure 1 This is a photograph of the state of the radiation cross-linked collagen fiber material obtained by Example 1 of the present invention; Figure 2 This is a photograph of the irradiated cross-linked collagen fiber material obtained in Example 3 of the invention after freeze-drying; Figure 3 It is a comparison chart of the remaining collagen fiber ratios of the irradiated cross-linked collagen fiber materials obtained by Examples 1 to 3 and Comparative Examples 1 to 10 after different enzymatic hydrolysis times. DETAILED DESCRIPTION
[0039] In order to make the technical solution of the present invention clearer, Figure 1 , Figure 2 , Figure 3 The present invention is further described in detail with reference to the accompanying drawings and specific embodiments.
[0040] Example 1, a method for preparing a radiation cross-linked collagen fiber material, comprising the following preparation steps: Collagen self-assembly precipitation: The acidic collagen solution extracted from animal sources was adjusted to pH 7.4, sodium chloride concentration 0.15M, solution temperature 37°C, and allowed to stand for 2.5 hours to simulate the collagen self-assembly process in vitro. The precipitated collagen fibers were then homogenized and dispersed and centrifuged to obtain concentrated collagen fibers.
[0041] Preparation of cross-linked collagen fibers: Redispersion of concentrated collagen fibers: Blend physiological saline and dimethyl sulfoxide at a ratio of 1:1 (v / v), and add 0.1% (w / v) Triton X-100 to the blended solution to form an irradiation solvent system. Disperse the concentrated collagen fibers homogeneously in the above irradiation solvent system at a liquid ratio of 1:40. The liquid ratio refers to the mass ratio of concentrated collagen fibers to the irradiation solvent system, such as 100g of collagen fibers dispersed in 4000g of irradiation solvent system. Stir for 30 minutes, then centrifuge to obtain collagen fiber intermediates, and control the collagen concentration to 35mg / ml.
[0042] Cross-linking of collagen fiber intermediates: the obtained collagen fiber intermediates were packaged in aluminum foil bags with a single bag thickness of 5 mm, and sealed by flattening: then electron beam irradiation cross-linking was performed at 20°C with an irradiation dose of 20 kGy to obtain cross-linked collagen fibers.
[0043] Preparation of irradiation cross-linked collagen fiber materials: Removal of dispersant: The cross-linked collagen fibers were re-dispersed in physiological saline at a liquid ratio of 1:20, and dispersed by homogenization for 30 minutes. After ultrasonic extraction for 60 minutes, the collagen fibers were obtained by centrifugation; the above ultrasonic cleaning was repeated 3 times, and the dispersant was not detected.
[0044] The cross-linked collagen fibers from which the dispersant has been removed are packaged in aluminum foil bags, each bag having a thickness of 8 mm, and are ultra-low temperature quick-frozen in a -80°C refrigerator.
[0045] Low-temperature irradiation sterilization: The ultra-low-temperature quick-frozen cross-linked collagen fibers are spread flat on dry ice for low-temperature irradiation sterilization, with an irradiation dose of 25 kGy.
[0046] Thawing: Place the cross-linked collagen fibers sterilized by low-temperature irradiation in a 25°C constant temperature box for 20 minutes to thaw, then shake for 1 minute and continue thawing for 20 minutes. Repeat 3 times until completely thawed to obtain a irradiated cross-linked collagen fiber gel with a slightly fluid state, and obtain an irradiated cross-linked collagen fiber material (appearance photo as shown in Figure 1 ).
[0047] Example 2, a method for preparing a radiation cross-linked collagen fiber material, comprising the following preparation steps: Collagen self-assembly precipitation: The acidic collagen solution extracted from animal sources was adjusted to pH 7.4, sodium chloride concentration 0.15M, solution temperature 37°C, and allowed to stand for 2.5 hours to simulate the collagen self-assembly process in vitro. The precipitated collagen fibers were then homogenized and dispersed and centrifuged to obtain concentrated collagen fibers.
[0048] Preparation of cross-linked collagen fibers: Re-dispersion of concentrated collagen fibers: physiological saline and acetone were mixed in a ratio of 3:7 (v / v), and 0.5% (w / v) Triton X-114 was added to the mixed solution to prepare an irradiation solvent system. The concentrated collagen fibers were homogeneously dispersed in the above irradiation solvent system at a liquid ratio of 1:40. After stirring for 30 min, the collagen fiber intermediates were obtained by centrifugation and the concentration was controlled to be 45 mg / ml.
[0049] Cross-linking of collagen fiber intermediates: The obtained collagen fiber intermediates were packaged in aluminum foil bags with a single bag thickness of 8 mm, and sealed by flattening; then, electron beam irradiation cross-linking was performed at 30° C. with an irradiation dose of 10 kGy to obtain cross-linked collagen fibers.
[0050] Preparation of irradiation cross-linked collagen fiber materials: Removal of dispersant: The cross-linked collagen fibers were re-dispersed in physiological saline at a liquid ratio of 1:50, and dispersed by homogenization for 30 min. After ultrasonic extraction for 30 min, the collagen fibers were obtained by centrifugation. The above ultrasonic cleaning was repeated 3 times, and the dispersant was not detected.
[0051] The cross-linked collagen fibers from which the dispersant has been removed are packaged in aluminum foil bags, each bag having a thickness of 5 mm, and are ultra-low temperature quick-frozen in a -80°C refrigerator.
[0052] Low-temperature irradiation sterilization: The ultra-low-temperature quick-frozen cross-linked collagen fibers are spread on dry ice for low-temperature irradiation sterilization, with an irradiation dose of 30 kGy.
[0053] Thawing: Place the cross-linked collagen fibers sterilized by low-temperature irradiation in a 25°C constant temperature box for 20 min to thaw, then shake for 1 min and continue thawing for 20 min. Repeat 3 times until completely thawed to obtain irradiated cross-linked collagen fiber materials.
[0054] Example 3, a method for preparing a radiation cross-linked collagen fiber material, comprising the following preparation steps: Collagen self-assembly precipitation: The acidic collagen solution extracted from animal sources was adjusted to pH 7.4, sodium chloride concentration 0.15M, solution temperature 37°C, and allowed to stand for 2.5 hours to simulate the self-assembly process of collagen in vitro. The precipitated collagen fibers were then homogenized and dispersed and centrifuged to obtain concentrated collagen fibers.
[0055] Preparation of cross-linked collagen fibers: Re-dispersion of concentrated collagen fibers: Physiological saline and isopropanol were mixed in a ratio of 2:3 (v / v), and 2% (w / v) Triton GR-7M was added to the mixed solution to obtain an irradiated solvent system. The concentrated collagen fibers were homogeneously dispersed in the irradiated solvent system at a liquid ratio of 1:40. After stirring for 30 min, the collagen fiber intermediates were obtained by centrifugation and the concentration was controlled to be 40 mg / ml.
[0056] Cross-linking of collagen fiber intermediates: The obtained collagen fiber intermediates were packaged in aluminum foil bags with a single bag thickness of 7 mm, and sealed by flattening; then, electron beam irradiation cross-linking was performed at 25°C with an irradiation dose of 15 kGy to obtain cross-linked collagen fibers.
[0057] Preparation of irradiation cross-linked collagen fiber materials: Removal of dispersant: The cross-linked collagen fibers were re-dispersed in physiological saline with a liquid ratio of 1:40. The fibers were dispersed by homogenization for 30 min. After ultrasonic extraction for 35 min, the collagen fibers were obtained by centrifugation. The above ultrasonic cleaning was repeated 3 times. No dispersant was detected.
[0058] The cross-linked collagen fibers from which the dispersant was removed were packaged in aluminum foil bags, each bag having a thickness of 6 mm, and were quickly frozen in a -80°C refrigerator.
[0059] Low-temperature irradiation sterilization: The ultra-low-temperature quick-frozen cross-linked collagen fibers are spread on dry ice for low-temperature irradiation sterilization, with an irradiation dose of 28 kGy.
[0060] Freeze drying: The collagen fibers sterilized by low temperature irradiation are directly freeze dried to obtain irradiated cross-linked collagen fiber materials. The state of the irradiated cross-linked collagen fiber materials is as follows: Figure 2 .
[0061] Comparative Example 1 is a method for preparing a radiation cross-linked collagen fiber material. The difference from Example 1 is that in the preparation of the cross-linked collagen fibers, an equal amount of physiological saline is used to replace the radiation solvent system.
[0062] Comparative Example 2 is a method for preparing a radiation cross-linked collagen fiber material, which is different from Example 1 in that in the collagen fiber intermediate cross-linking step, the thickness of a single aluminum foil bag is 10 mm.
[0063] Comparative Example 3, a method for preparing a radiation cross-linked collagen fiber material, is different from Example 1 in that the collagen concentration of the collagen fiber intermediate in the concentrated collagen fiber redispersion step is 55 mg / ml.
[0064] Comparative Example 4 is a method for preparing a radiation cross-linked collagen fiber material. The difference from Example 2 is that in the collagen fiber intermediate cross-linking step, the radiation cross-linking is controlled at a dosage of 25 kGy.
[0065] Comparative Example 5 is a method for preparing a radiation cross-linked collagen fiber material. The difference from Example 2 is that in the collagen fiber intermediate cross-linking step, the radiation cross-linking is controlled at a dosage of 5 kGy.
[0066] Comparative Example 6 is a method for preparing a radiation cross-linked collagen fiber material. The difference from Example 2 is that in the collagen fiber intermediate cross-linking step, the radiation cross-linking is performed in a -20°C frozen state.
[0067] Comparative Example 7, a method for preparing an irradiated cross-linked collagen fiber material, differs from Example 1 in that, in the step of removing the dispersant, three homogenization and ultrasonic extraction and cleaning are not used. Specifically, the cross-linked collagen fibers are redispersed in physiological saline with a liquid ratio of 1:20, and the collagen fibers are obtained by centrifugation, followed by low-temperature irradiation sterilization.
[0068] Comparative Example 8, a method for preparing an irradiated cross-linked collagen fiber material, is different from Example 1 in that dry ice is not used in the low-temperature irradiation sterilization step, and irradiation is not performed at a low temperature. The specific operation is as follows: The ultra-low temperature quick-frozen cross-linked collagen fibers were packaged in aluminum foil bags with a single bag thickness of 8 mm and placed at room temperature of 20°C. They were then irradiated for sterilization with an irradiation dose of 25 kGy.
[0069] Comparative Example 9: A method for preparing an irradiated cross-linked collagen fiber material. The difference from Example 1 is that in the preparation of the cross-linked collagen fibers, the solvent is only a mixture of physiological saline and dimethyl sulfoxide in a ratio of 1:1 (v / v), and no dispersant Triton X-100 is added.
[0070] Comparative Example 10 is a method for preparing a radiation cross-linked collagen fiber material. The difference from Example 1 is that in the preparation of the cross-linked collagen fibers, the radiation solvent system used is not mixed with dimethyl sulfoxide, but is equal amounts of physiological saline and TritonX-100.
[0071] Performance Test: Experimental samples: The irradiated cross-linked collagen fiber materials prepared by the preparation methods of the irradiated cross-linked collagen fiber materials of Examples 1 to 3 and Comparative Examples 1 to 10 were used as experimental samples, and the injection performance, enzymatic resistance, cross-linking degree and solvent residue of the materials were tested. The specific experimental process and experimental results are as follows: 1. Material injection performance The experimental samples were divided into syringes, and a 27 G syringe needle was used to measure the sample push injection situation by a universal tensile machine. The push speed was set to 30 mm / min, and the maximum push force during the push process was set to 25 N. If the push force during the whole process of sample pushing was less than 25 N, the sample was considered qualified; if the push force during the measurement was greater than 25 N or needle blockage occurred, it was considered unqualified. The specific experimental results are shown in Table 1.
[0072] Table 1. Injection properties of radiation cross-linked collagen fiber materials obtained using Examples 1 to 3 and Comparative Examples 1 to 10
[0073] According to the results in the above table, the collagen fiber materials prepared in Examples 1 and 2 can pass smoothly through 27 G The syringe needle can be injected evenly without needle blockage; Comparative Example 1 had needle blockage, which was due to the fact that no solvent and dispersant solvent system were used before the radiation cross-linking process, resulting in collagen aggregation during the radiation process and local excessive cross-linking, and the subsequent homogenization could not thoroughly disperse the collagen evenly; Comparative Example 2 had a high pushing force and was unqualified, which was due to the high stacking thickness of the material and uneven electron beam irradiation during the radiation cross-linking; Comparative Example 3 had an excessively high pushing force and was unqualified, which was due to the excessively high collagen concentration before radiation cross-linking, resulting in uneven cross-linking and local excessive cross-linking; Comparative Example 4 had needle blockage, which was due to the excessively high dose of radiation cross-linking, resulting in local rapid cross-linking of collagen fibers and uneven material; Comparative Examples 5 and 6 had qualified pushing forces; Comparative Example 7 had a high pushing force, which was due to the lack of homogenization ultrasonic treatment, resulting in local cross-linking of the irradiated collagen fibers and inability to be smoothly injected; Comparative Example 8 had needle blockage, which was due to radiation cross-linking at room temperature, resulting in secondary cross-linking and fiber entanglement. Comparative Examples 9 and 10 showed needle blocking phenomenon. This was because no dispersant and organic solvent were used in the solvent system during the radiation cross-linking process, which resulted in excessive cross-linking of the collagen fibers and needle blocking.
[0074] 2. Particle size determination The sample was diluted 50 times with normal saline, and the average particle size of the collagen fibers in the solution was tested by dynamic light scattering. All sample solutions were added to polystyrene cuvettes for detection. The average particle size distribution range of collagen fibers in normal saline can be analyzed by dynamic light scattering. The collagen fibers in the solution will scatter the light passing through, and the mutual superposition of scattered light will cause the superposition or reduction of the light intensity in the dark and bright areas of the particles, so that the light intensity presents a fluctuating form. Under the irradiation of the laser, the scattered light intensity of the moving particles will also fluctuate. The frequency of the fluctuation is related to the size of the particles. The changes in the speed of ion fluctuations are recorded by dynamic light scattering to obtain the particle size distribution information of the particles in the solution. As shown in the following table, the average particle size distribution results of the samples are shown in Table 2.
[0075] Table 2. Average particle sizes of irradiated cross-linked collagen fiber materials obtained using Examples 1 to 3 and Comparative Examples 1 to 10
[0076] According to the results in the above table, the average particle size of the collagen fiber material prepared in Examples 1 and 2 is between 100 and 150 microns, which meets the injection requirements; the average particle size of Comparative Example 1 reaches 434.44±109.46 microns, and the particle size is too large and uneven. This is because no solvent and dispersant solvent system are used before the radiation cross-linking process, which causes collagen aggregation during the irradiation process and leads to local excessive cross-linking. The average particle size of Comparative Example 2 is higher than 150 microns, which is caused by the high stacking thickness of the material and uneven electron beam irradiation during irradiation cross-linking; the average particle size of Comparative Example 3 is 348.11 microns, and the fluctuation is large, which is caused by the excessively high collagen concentration before irradiation cross-linking, resulting in uneven cross-linking and excessive local cross-linking; Comparative Example 4 is unqualified because the collagen fibers are locally rapidly cross-linked due to the excessive dose of irradiation cross-linking; the average particle size of Comparative Examples 5 and 6 is less than 100 microns, which is caused by insufficient cross-linking; the average particle size of Comparative Example 7 is greater than 150 microns, which is caused by the lack of homogenization ultrasonic treatment; the average particle size of Comparative Example 8 is 337.65 microns, which is caused by secondary cross-linking and fiber entanglement due to irradiation cross-linking at room temperature. The average particle size of Comparative Example 9 is greater than 150 microns, which is caused by the lack of dispersant in the solvent system; the average particle size of Comparative Example 10 is 234.75±67.19 microns, which is caused by the partial excessive cross-linking of collagen fibers due to the lack of organic solvent in the solvent system.
[0077] 3. Material resistance to enzymatic hydrolysis The collagen fiber samples prepared in the comparative example and the example were placed in 10 ML centrifuge tubes, 4 g in each centrifuge tube, and 100 U / ml type I collagenase hydrolyzate was added, and water bath hydrolysis was performed at 37 degrees Celsius. Six samples were set for each group of samples, and centrifuged to obtain precipitates after different hydrolysis times. The precipitates were weighed to calculate the proportion of the remaining collagen fibers, and the enzymatic hydrolysis resistance of the material was obtained.
[0078] The results are as follows Figure 3As shown: Examples 1 and 2 have a relatively high level of resistance to enzymolysis; Comparative Example 1 has a slightly poorer resistance to enzymolysis; Comparative Examples 2 and 3 have a relatively high thickness and a relatively high material concentration during irradiation crosslinking, which results in a decreased degree of crosslinking and poor resistance to enzymolysis; Comparative Example 4 has a relatively high degree of crosslinking and a relatively high resistance to enzymolysis due to an increased irradiation dose; Comparative Example 5 degrades relatively quickly, which is due to a relatively low irradiation dose and insufficient degree of crosslinking; Comparative Example 6 has the fastest degradation rate, which is due to the fact that the irradiation crosslinking process is carried out at low temperature crystallization and the collagen material has no fluidity, so the irradiation crosslinking effect is very poor; Comparative Example 7 does not use ultrasonic cleaning, which has no effect on the degree of irradiation crosslinking; Comparative Example 8 has the strongest resistance to enzymolysis due to the use of room temperature in the second irradiation sterilization process, and the secondary crosslinking results in the strongest resistance to enzymolysis. Comparative Examples 9 and 10 have excessive local crosslinking due to the irradiation crosslinking system, and have no significant reduction in enzymolysis capacity.
[0079] 4. Cross-linking degree The degree of cross-linking of the material is determined by measuring the number of free amino groups of the experimental object. The degree of cross-linking of the material is determined by measuring the number of free amino groups of the sample. Three parallel samples are measured for each group of samples. The results of the cross-linking degree determination of the material are shown in Table 3.
[0080] The test method for crosslinking degree is as follows: Standard curve drawing: Accurately weigh 75 mg of glycine and dissolve it in 10 ml of water to obtain a 0.1 M glycine solution. Pipette the 0.1 M glycine solution and dilute it to 10 ml to prepare a 0.25-2.50 mM glycine standard solution and determine the standard curve.
[0081] Add 1.2 ml Buffer (0.05 mol / L borax, pH 10) to 0.150 ml glycine standard solution, and then add 1.2 ml TNBS solution. Place the test tube in a dark 50 ℃ water bath for 60 min. Add 1.4 ml deionized water, then add 1 ml 0.1 mol / L hydrochloric acid, cool at room temperature for 30 min, and measure the absorbance at 340 nm.
[0082] Use water as blank solution. Quartz cuvette is required.
[0083] A standard curve was drawn with free amino group concentration (mM) as the abscissa and absorbance as the ordinate.
[0084] 1. Sample determination The sample concentration to be measured is between 0.25 and 2.50 mM, and the free amino group concentration of the sample solution is calculated based on the standard curve.
[0085] 2. Calculation of collagen cross-linking degree Free amino content (umol / mg) = free amino concentration / protein concentration Crosslinking degree = (free amino content before modification - free amino content after modification) / free amino content before modification * 100% Theoretical value of free amino content before modification: 0.25umol / mg.
[0086] Table 3. List of crosslinking degrees of irradiated crosslinked collagen fiber materials obtained using Examples 1 to 3 and Comparative Examples 1 to 10
[0087] The results of the cross-linking degree of the material are basically consistent with the resistance to enzymolysis. The higher the cross-linking degree of the material, the stronger its resistance to enzymolysis. The cross-linking degree of Examples 1-3 is between 87-89%. The cross-linking degree of Comparative Example 1 fluctuates greatly. This is due to the uneven cross-linking caused by the lack of a dispersed solvent system; the cross-linking degree of Comparative Examples 2 and 3 decreases due to the high thickness and high concentration of the material; the cross-linking degree of Comparative Example 4 is very high, which is caused by the high irradiation dose used; the cross-linking degree of Comparative Example 5 is low, which is caused by the low irradiation dose; Comparative Example 6 is irradiated and cross-linked at low temperature, and the collagen fibers cannot move after freezing, resulting in a significant reduction in its cross-linking degree; Comparative Example 7 does not use ultrasonic cleaning, which has no obvious effect on the cross-linking degree of the material; Comparative Example 8 has a high degree of cross-linking due to secondary irradiation cross-linking. Comparative Examples 9 and 10 do not use dispersants and organic solvents in the irradiation system, resulting in rapid and uneven irradiation cross-linking, so the cross-linking degree is relatively high.
[0088] 5. Solvent residue The qualification of the product is determined by measuring the residual organic solvent and dispersant used in the test sample. The residual solvent is determined by measuring the residual concentration in the extract after extraction.
[0089] Table 4. List of solvent residue results of radiation cross-linked collagen fiber materials obtained using Examples 1 to 3 and Comparative Examples 1 to 10
[0090] From the above results, it can be seen that during the preparation process of collagen fibers, if homogenization and ultrasonic treatment are repeated 3 times, the organic solvent and dispersant in the final product are washed away and not detected; only the residue is detected in Example 7, which is unqualified.
[0091] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the patent of the present invention. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A method for preparing a radiation cross-linked collagen fiber material, characterized in that: The steps include: (1) Preparation of collagen fiber intermediates: Dispersing concentrated collagen fibers in an irradiated solvent system, and obtaining collagen fiber intermediates with a concentration of 35-45 mg / ml after centrifugation; the irradiated solvent system comprises physiological saline and an organic solvent in a volume ratio of 1:(1-2.4), and a dispersant with a total amount of 0.1-2 w / v% of the physiological saline and the organic solvent; (2) irradiation cross-linking: irradiating and cross-linking the collagen fiber intermediate at a temperature of 20-30° C. and an irradiation dose of 10-20 kGy to obtain cross-linked collagen fibers; (3) removing the dispersant from the cross-linked collagen fibers and sterilizing them by low-temperature irradiation to obtain a finished collagen fiber material.
2. The method for preparing a radiation cross-linked collagen fiber material according to claim 1, characterized in that: The concentrated collagen fibers include any one or more combinations of type I collagen fibers, type II collagen fibers, and type III collagen fibers.
3. The method for preparing a radiation cross-linked collagen fiber material according to claim 1, characterized in that: The radiation crosslinking is electron beam irradiation or gamma ray irradiation.
4. The method for preparing a radiation cross-linked collagen fiber material according to claim 3, characterized in that: Electron beam irradiation is adopted, and the thickness of the collagen fiber intermediate does not exceed 10 mm during irradiation.
5. The method for preparing a radiation cross-linked collagen fiber material according to any one of claims 1 to 4, characterized in that: The organic solvent includes any one or more combinations of dimethyl sulfoxide, isopropanol, acetone, ethyl acetate, and methyl tert-butyl ether.
6. The method for preparing a radiation cross-linked collagen fiber material according to claim 5, characterized in that: The dispersant includes any one or more combinations of Triton X-100, Triton X-114, Triton X-405, and Triton GR-7M.
7. A method for preparing a radiation cross-linked collagen fiber material according to any one of claims 1 to 4 or 6, characterized in that: The method for removing the dispersant in step (3) includes: re-dissolution, homogenization and / or ultrasonic treatment, and centrifugation.
8. The method for preparing a radiation cross-linked collagen fiber material according to claim 7, characterized in that: The method for removing the dispersant in step (3) comprises: adding physiological saline to the cross-linked collagen fibers, controlling the liquid ratio to be 1:20-1:50, homogenizing and dispersing for 30 minutes, ultrasonically extracting for 30-60 minutes, and centrifuging; and repeating the operation multiple times.
9. The method for preparing a radiation cross-linked collagen fiber material according to any one of claims 1 to 4 or 6, characterized in that: The cross-linked collagen fibers are first subjected to ultra-low temperature quick freezing treatment, and then subjected to low-temperature irradiation sterilization treatment at a temperature range of -40-80°C; the irradiation dose of the low-temperature irradiation sterilization treatment is 25-30 kGy.
10. Collagen fiber material prepared by the method according to any one of claims 1 to 9.
11. The collagen fiber material according to claim 10, characterized in that: The degree of cross-linking of the material is between 85% and 90%.
12. The collagen fiber material according to claim 10, characterized in that: The average particle size of the collagen fibers is in the range of 100-150 μm.
13. The collagen fiber material according to claim 10, characterized in that: The material was filled into a 27 G syringe, and the maximum pushing force was between 11.5 N and 25 N at a pushing speed of 30 mm / min.
14. Use of the collagen fiber material according to any one of claims 10 to 13 in the preparation of medical injection filling materials and / or tissue engineering scaffolds.
Citation Information
Patent Citations
Acellular matrix particle filler and preparation method thereof
CN114949359A
Injectable composite microgel capable of promoting regeneration of collagen as well as preparation and application of injectable composite microgel
CN116492290A
Gradient mineralized collagenous fiber membrane as well as preparation method and application thereof
CN119113215A
Collagen molded body and method for producing the same
JP2014218453A
Electron-beam sterilization of biological materials
US5989498A
Cited By
Irradiation crosslinking collagen injection filler as well as preparation method and application thereof
CN121623000A
Irradiated cross-linked collagen injectable filler and methods of making and using the same
CN121623000B